Evidence of Increased Hydrophobicity and Dynamics inside the Tail Region of Glycolipid Self-Assemblies Using 2-n-Alkyl-Pyrene Derivatives to Probe Different Locations - Zahid, Noor Idayu Mat; Ji, Lei; Khyasudeen, M. Faisal; Friedrich, Alexandra; Hashim, Rauzah; Marder, Todd B.; Abou-Zied, Osama K. (American Chemical Society, 2019)
New designer biofluorophores are being increasingly used in the investigation of complex cellular processes. In this study, we utilized new derivatives of pyrene (Py), i.e., 2-n-alkyl-pyrenes (Py-C4 and Py-C8), in order to probe different regions inside the hydrophobic tail of n-dodecyl β-d-maltoside (βMal-C12) in two different phases (cubic ↔ lamellar). Although the sensitivity to the local environment is reduced compared to that of Py, attaching C4 and C8 at the 2-position of Py can provide a possible means to probe the local hydrophobicity in different parts of the tail region. The absence of excimer fluorescence and the ratio of the vibronic fluorescence peak intensities (I1/I3) in a lipid environment indicate the existence of Py as monomers in the hydrophobic region, similar to hydrophobic solvation, yet close to the headgroup region. When Py is replaced by Py-C4 and Py-C8, there is a small increase in hydrophobicity (reduction in I1/I3) as the Py moiety is pulled deeper inside the tail region of both cubic and lamellar phases. The larger space of the tail region in the lamellar phase is reflected as more local hydrophobicity measured by the probes which can penetrate deep inside, whereas the curved structure of the cubic phase limits the available space for the probes. Three fluorescence lifetime components were measured in lipid, indicating the heterogeneous nature of the hydrophobic region. In the lamellar phase, a large reduction in the average lifetime value, led by the long decay component, was measured for Py-C4 (reduction by 25%) and Py-C8 (45%) compared to that of the parent Py. This observation suggests the presence of a mechanism of interaction more collisional than static between the Py moiety and the tail region of the bilayer unit due to the ample space provided by the lamellar phase as the probe is buried deeper inside the hydrophobic region. A much smaller effect was observed in the cubic phase and was correlated with the tight environment around the probes, which stems from the increased curvature of the cubic phase. The current results provide a deeper understanding of the hydrophobic region during phase transition of lipid self-assembly which is important for better control during the process of membrane-protein crystallization.